2004
DOI: 10.1016/j.ehj.2003.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Smoking decreases the duration of life lived with and without cardiovascular disease: a life course analysis of the Framingham Heart Study

Abstract: Smoking, by shortening life, decreases both the probability and duration of cardiovascular disease throughout the life course. Non-smokers live many years longer and longer free of cardiovascular disease than smokers, but at the end of their life non-smokers will have lived longer with cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 11 publications
7
55
0
2
Order By: Relevance
“…Smoking contributes strongly to cancer of the lung, COPD, and cancer of the upper respiratory and digestive system; and to a lesser extent to coronary heart disease, stroke, and cancer of the bladder, stomach, kidney, and pancreas (U.S. Department of Health and Human Services 2004). Several studies have found large gaps in the life expectancies of smokers and non-smokers, amounting to between six and 10 years (Doll et al 2004, Mamun et al 2004, van Baal et al 2006. Within Europe, smoking is the leading risk factor for premature mortality, and it has the greatest impact on the disease burden of all of the preventable lifestyle factors (World Health Organization 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking contributes strongly to cancer of the lung, COPD, and cancer of the upper respiratory and digestive system; and to a lesser extent to coronary heart disease, stroke, and cancer of the bladder, stomach, kidney, and pancreas (U.S. Department of Health and Human Services 2004). Several studies have found large gaps in the life expectancies of smokers and non-smokers, amounting to between six and 10 years (Doll et al 2004, Mamun et al 2004, van Baal et al 2006. Within Europe, smoking is the leading risk factor for premature mortality, and it has the greatest impact on the disease burden of all of the preventable lifestyle factors (World Health Organization 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Whether, for example, higher levels of physical activity would reduce the number of years lived with diabetes depends on the balance of its effect on the risks of developing diabetes and mortality. For instance, it has been shown that nonsmokers live longer with cardiovascular disease than smokers because their total life expectancy is ϳ8 years longer (22). As policy makers increasingly advocate modification of risk factors with the aim of decreasing population levels of disease and disability (e.g., 23), it will be important to analyze the extent to which this is actually the case.…”
mentioning
confidence: 99%
“…The Heart and Estrogen/Progestin Replacement Study (HERS [37]) showed smoking to be a predictor for the development of heart failure in women with established heart disease. A direct and independent relationship has been observed between smoking and the development of asymptomatic ventricular dysfunction (38)(39)(40). A dose-response relationship has also been found between the number of pack-years of smoking and reduced regional LV function in asymptomatic individuals (40).…”
Section: Smokingmentioning
confidence: 86%